Satisfacción laboral en médicos de hospitales del sector público y semiprivado. Trujillo - 2009 - Sánchez Cortéz, Cristian Celso (2010)
Introduction. The great challenge for all health organization is finding ways to meet the needs of others, physicians in our case. It should be noted that job satisfaction in physicians has been poorly studied, much less have compared its actual state in both public and semi-public systems of health. Objectives. Compare physicians’s job satisfaction in hospitals of public and semi-public sectors, globally and for each dimension that conform. Besides determining the correlation between characteristics such as age, gender, time of service and employment conditions with the job satisfaction. Material and Methods. Ninety-four surveys were conducted at the physicians staff who perform their work in Víctor Lazarte Echegaray (HVLE) y Belén de Trujillo (HBT) hospitals, with more than four years of work in the institution. Data were loaded into SPSS v5.0 and Excel spreadsheets. We used an Observational - Comparative Descriptive study design. Results. 89% respondents physicians of HVLE and 95% of HBT showed global job dissatisfaction. In both hospitals is shown that the dimension has more influence in job satisfaction corresponds to the "Current Work" and "General Work." Dissatisfaction was evident in the dimensions of "Opportunities for Progress" and "Compensation and Incentives." Conclusion. Physicians’s job dissatisfaction is evident in both hospitals Víctor Lazarte Echegaray (semi-private sector) and Belén de Trujillo (public sector), without significant differences (p> 0.05).